Effect of Grape Seed Extract on Biochemical Factor and Histological Changes in Liver and the Kidney in Albino Rat Infected Hypo- Hyperthyroidism Induced Laboratory by Carbimazole and L-Thyroxine - Ahmed Jassem Al-Naely (Journal of Global Pharma Technology, 2017)
The aim of the current study was showing the effect of hypothyroidism and hyperthyroidism on some physiological parameters (creatinine and urea) and the concentration of amine transfer enzymes (AST, ALT, and ALP) also the histological structure of liver and kidney in albino rat, and role of grape seed extract (GSE) in protecting the liver and kidney tissue against thyroid disorders and improve the level, creatinine, urea, AST, ALT, and ALP. Study experiment samples consist of 80 rats divided into two main groups hypothyroidism and hyperthyroidism, each group includes five treatments. Carbimazole was used in 30 mg/kg dose to induce hypothyroidism and L-thyroxin in 20 mg/kg dose to induce hyperthyroidism. Results showed that a significant increased (P<0.05)concentrations of creatinin, urea, AST,ALT in hypothyroidism and hyperthyroidism groups compare with control, ALP significant increased (P<0.05)in hyperthyroidism while showed significant decreased (P<0.05)in hypothyroidism compare with control, treatment with GSE in both groups showed significant differences in concentration of urea, creatinin, AST, ALT, ALP and improved liver and kidney tissue compare with hypothyroidism and hyperthyroidism treatments. It was concluded from this study that extract of grape seeds has a protective role for the liver and kidney against damage caused by thyroid disorders and its treatments.Keywords: Grape seed extract, Thyroid, Liver, Kidney, Carbimazole, L-Thyroxin, Hypothyroidism, Hyperthyroidism.